SOSIALISASI PLATFORM KURIKULUM M PLATFORM KURIKULUM MERDEKA MENGAJAR KEPADA PARA GURU DI SDN 3 WATESNEGORO: KEPADA PARA GURU DI SDN 3 WATESNEGORO - Feri Tirtoni; Supriyadi; Ika Ratna Indra Astutik; Joko Susilo; Fika Fatmala (Universitas PGRI Adi Buana Surabaya, 2023)
This Community Service activity aims to find out how t use the Merdeka Teaching Platform which is addressed to the principal and all teachers at SDN Watesnegoro 3. The independent teaching curriculum suports many innovations in the world of education, especially progress in various educational instituitions including schools or madrasas, by building teacher competency. Therefore this study uses training and outreach methods. Where this research was carried out by socializing to the principal and teacher about the use of the independent teaching platform which was carried out at SDN Watesnegoro 3. The results showed that the socialized carried out to schol princials and teacher received a positive response in the form of enthusiasm from the school community regarding the indeendent teaching curriculum platform.